Trait association and diversity in exotic lines of Indian mustard - Ravindra Kumar; Ramandeep Kaur; Ikbal Singh; Satveer Kaur; Harjinder Singh (Journal of Oilseed Brassica, 2026)
Total 41 exotic lines of Indian mustard (Brassica juncea L.) were evaluated during winter 2016-17 under irrigatedenvironments. The genetic variability, heritability and genetic advance as percentage of mean for nine quantitativecharacters viz. plant height, number of primary branches number of primary branches, number of siliquae per plant,siliqua length (cm), number seeds per siliqua, number of seeds per plant, total seed yield (g) and test weight (g). Analysisof variance showed significant differences among the accession for all characters under study. Path coefficient analysiswas carried out using correlation coefficients to know the yield contributing traits having true associations with seedyield. Improvement in seed yield can be achieved by selection using the correlation and path analysis data generated inthis study. Total seed yield/ plant was positively correlated with siliqua length. Number of seeds/ plant and test weighthad higher phenotypic direct effects on total seed yield/ plant, revealing that indirect selection for these traits would beeffective in improving seed yield. The high heritability coupled with high genetic advance for test weight would also beof great use for indirect selection for improvement in seed yield. The material used in the study is of diverse nature andcan be used in the breeding programme for development of improved genotypes in mustard.